2007
DOI: 10.1007/s10804-007-9027-2
|View full text |Cite
|
Sign up to set email alerts
|

Religious Doubt and Mental Health Across the Lifespan

Abstract: The current study examined the connections among religious doubt, mental health, and aging in a nationwide sample of individuals 18 years and older (N = 1629). Findings indicate that that religious doubt emerging from the recognition of suffering and evil in the world has a deleterious impact on mental health. Results also show that as people grow older, religious doubts continue to be associated with psychopathology, but the magnitude of this association becomes weaker across age categories. In other words, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 37 publications
4
69
0
Order By: Relevance
“…Since open questioning and skepticism are discouraged within many religious groups, individuals who experience such doubts may be reluctant to express them, heightening their sense of isolation and struggle. The findings of several studies are consistent with this line of argument, showing that religious doubts are associated with elevated levels of psychological distress and psychiatry symptoms, and inversely associated with life satisfaction and other indicators of well-being (Ellison 1991;Galek et al 2007;Krause et al 1999;Krause 2006;Krause and Wulff 2004).…”
Section: Spiritual Strugglessupporting
confidence: 69%
“…Since open questioning and skepticism are discouraged within many religious groups, individuals who experience such doubts may be reluctant to express them, heightening their sense of isolation and struggle. The findings of several studies are consistent with this line of argument, showing that religious doubts are associated with elevated levels of psychological distress and psychiatry symptoms, and inversely associated with life satisfaction and other indicators of well-being (Ellison 1991;Galek et al 2007;Krause et al 1999;Krause 2006;Krause and Wulff 2004).…”
Section: Spiritual Strugglessupporting
confidence: 69%
“…To be sure, some prominent theologians (e.g., Paul Tillich) and developmental scholars (e.g., James Fowler) have argued that doubts can play a constructive role, leading to spiritual growth and maturation of faith (Krause et al 1999). However, a growing body of evidence links unresolved doubts with a range of negative mental and physical health outcomes (Ellison 1991;Galek et al 2007;Krause 2006;Krause and Ellison 2009;Krause et al 1999;Krause and Wulff 2004).…”
Section: Intrapsychic Struggles: Chronic Religious Doubtingmentioning
confidence: 99%
“…Indeed, previous research suggests that general nonbeliever samples and Christians experience similar levels of doubt-related struggles (Exline et al 2014;Stauner et al 2016). Among believers, religious doubt is not an uncommon phenomenon, and it is linked to poorer mental health (Galek et al 2007;Krause 2003) and physical health (Krause and Wulff 2004) outcomes. However, analyses of a subset of the samples analyzed in the present study indicated that doubt struggles predict higher life satisfaction and lower levels of depression after controlling for other types of R/S struggles (with theists and atheists pooled as one sample; Exline et al 2014).…”
Section: Religious and Spiritual Strugglesmentioning
confidence: 99%